PENENTUAN GELOMBANG SOLITON PADA FIBER BRAGG GRATING DENGAN MENGGUNAKAN METODE STEP-SPLIT - Siahaan, Theresa Febrina; ', Saktioto; Edisar, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The determination of wave solitons in Fiber Bragg Grating by using the Step- MethodSplit has been done. This research was conducted by simulating wave using computer software namely MATLAB R2011a. The wave soliton model then used parameters such as the alpha value of 0.75 dB/km, 1 dB/km, betha value of 0.75 ps2/km, and gamma value0.25 W-1 km-1, 0.5 W-1 km-1. The results obtained from this parameter changes produced in the form of voltage amplitude to see potential changes in wave soliton. This research also aims to solve Nonlinear Schrodinger Equation by using the Step Method-Split that can be solved by changing the parameters such as the value of the Fourier with a value of 200 and 300 and 15 ps window size, resulting in a 20 ps. The simulation input and output power of a soliton solve with a nonlinear Kerr effect. The effects of dispersion can be compensated so as to obtain a steady pulse.